Frequency of HIV among patients seeking antenatal care at a tertiary care hospital, Karachi - Akhtar, Omema; Qazi, Osama; Dr. Haleema Yasmin; Dr. Khadija Bano; Qamar, Dr. Sabiha (Journal of the Pakistan Medical Association, 2022)
Objective: To determine the frequency of human immunodeficiency virus among pregnant women reporting for antenatal care at a tertiary care hospital. Method: The cross-sectional study was conducted at Unit-1 of the Department of Obstetrics and Gynaecology, Jinnah Postgraduate Medical Centre, Karachi, from August 2018 to January 2019, and comprised all women attending antenatal clinics aged 15-40 years having gestational age of at least 10 weeks confirmed by trans-vaginal/trans-abdominal scan. Data was collected using a predesigned questionnaire. Data was analysed using SPSS 21. Results: There were 642 pregnant women with a mean age of 25.80±4.91 years, and mean gestational age of 24.34±5.38 weeks. Of the total, 5(0.7%) subjects had family history of human immunodeficiency virus and 1(0.2%) had a positive result for the virus. There was significant association of human immunodeficiency virus with family history of the disease (p=0.001) and with history of drug abuse (p=0.003) Conclusion: Screening of human immunodeficiency virus during the antenatal period is a useful tool for better management. Key Words: HIV, Pregnancy, Prevalence.